GeneMatch: A novel recruitment registry using at‐home APOE genotyping to enhance referrals to Alzheimer's prevention studies. Issue 4 (13th February 2019) - Langbaum, Jessica B.; Karlawish, Jason; Roberts, J. Scott; Wood, Elisabeth M.; Bradbury, Angela; High, Nellie; Walsh, Trisha L.; Gordon, David; Aggarwal, Raj; Davis, Peter; Stowell, Carter; Trisko, Lane; et al.
Abstract: Introduction: Recruitment for Alzheimer's disease (AD) prevention research studies is challenging because of lack of awareness among cognitively healthy adults coupled with the high screen fail rate due to participants not having a genetic risk factor or biomarker evidence of the disease. Participant recruitment registries offer one solution for efficiently and effectively identifying, characterizing, and connecting potential eligible volunteers to studies. Methods: Individuals aged 55‐75 years who live in the United States and self‐report not having a diagnosis of cognitive impairment such as MCI or dementia are eligible to join GeneMatch. Participants enroll online and are provided a cheek swab kit for DNA extraction and apolipoprotein E ( APOE ) genotyping. Participants are not told their APOE results, although the results may be used in part to help match participants to AD prevention studies. Results: As of August 2018, 75, 351 participants had joined GeneMatch. Nearly 30% of participants have one APOE4 allele, and approximately 3% have two APOE4 alleles. The percentages of APOE4 heterozygotes and homozygotes are inversely associated with age ( P  < .001). Discussion: GeneMatch, the first trial‐independent research enrollment program designed to recruit and refer cognitively healthy adults to AD prevention studies based in part on APOE test results, provides a novel mechanism to accelerate prescreening and enrollment for AD prevention trials.